Ethnobotanical Study of the Use of Soursop Leaves (Annona muricata L.) as Traditional Medicine in Lagosi Village, Wajo Regency - Juliasti. A, Hielda; Rompegading, Andi Badli; Ferawati; Risna; Arfiani, Besse (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
This study is an ethnobotanical study that aims to describe and analyze the use of soursop leaves (Annona muricata L.) as traditional medicine by the community of Lagosi Village, Wajo Regency. The research method used is qualitative descriptive with data collection techniques through semi-structured interviews with informants selected purposively. The results of the study indicate that soursop leaves are used to treat swelling caused by sprains, headaches, and high blood pressure. The methods of use include rubbing the leaves in one direction on the swollen part of the body, the traditional practice of ma'boso for headaches, and boiling the leaves to drink as a blood pressure reducer. Knowledge about the use of soursop leaves is passed down orally from generation to generation and is part of the local wisdom of the Lagosi community. This study emphasizes the importance of documenting traditional knowledge to preserve cultural heritage and as a foundation for further research in the development of natural medicines based on local plants.